2019
DOI: 10.2298/gensr1901213e
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide diversity of Cyt b gene in drosophila subobscura Collin

Abstract: Mitochondrial DNA variability of Drosophila subobscura Collin from Southeastern Serbia was studied with respect to Restriction Site Analysis (RSA) of complete mitochondrial genome and the nucleotide sequence of Cytochrome b (Cyt b) gene. The aim was to shed more light on the evolutionary forces that shape mtDNA variation of this species. Samples were collected from two sites in the foothills of the Balkan Mountains. No genetic differentiation was found between groups and most of the variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The present study is in accordance with the previously published articles on family Lamiaceae taxa (ZAHRA et al, 2016;(CURTO et al, 2012). Some other studied on family Lamiaceae have been done utilizing the genetic diversity through short sequencing for delimitation of the taxa in the family through using DNA barcoding (ERIĆ et al, 2019;SEVINDIK, 2019). These selected species we studied in the present work showed that they are paraphyletic which have been studied in the previous work on Lamiaceae (SCHEEN et al, 2009).…”
Section: Phylogenetic Tree Based On Nucleotide Sequences Of Rps14supporting
confidence: 89%
See 1 more Smart Citation
“…The present study is in accordance with the previously published articles on family Lamiaceae taxa (ZAHRA et al, 2016;(CURTO et al, 2012). Some other studied on family Lamiaceae have been done utilizing the genetic diversity through short sequencing for delimitation of the taxa in the family through using DNA barcoding (ERIĆ et al, 2019;SEVINDIK, 2019). These selected species we studied in the present work showed that they are paraphyletic which have been studied in the previous work on Lamiaceae (SCHEEN et al, 2009).…”
Section: Phylogenetic Tree Based On Nucleotide Sequences Of Rps14supporting
confidence: 89%
“…DNA sequences have become a major source of collecting information. Thus, researchers have examined the idea that an easy and rapid way of species identification and defining species boundaries is possible with the use of short DNA sequence (ERIĆ et al, 2019;SEVINDIK, 2019), which possess a standardized position in the genome, called as DNA barcode (HEBERT et al, 2004;FRÉZAL and LEBLOIS, 2008). DNA barcoding is a new approach designed to provide rapid, accurate and automatable species identification by using short standardized gene regions as internal species tags (AKINRO et al, 2019;GRITSENKO et al, 2019;PATI et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although SNPs do occur within each of the two haplotype groups, such SNPs are rare (e.g. [59]) and are not consistently polymorphic.…”
Section: Sequencing and Mitogenome Assembliesmentioning
confidence: 99%
“…Our results show that D. obscura possesses a high level of mtDNA variation both within and between populations. The nucleotide diversity within populations observed for the D. obscura Cyt b gene (0.00146-0.00387) is generally higher compared to other Drosophila species: D. melanogaster (0.0009), D. simulans (0.0003), D. yakuba (0.0014) (Ballard & Kreitman, 1994) and D. subobscura (0.00087) (Erić et al, 2019). Sequences form a complex haplotype network with several star-shaped subnetworks, with a geographical structuring of genetic variation across Europe, mostly across the East-West axis.…”
Section: Discussionmentioning
confidence: 92%
“…A PCR assay using 16S rDNA Wolbachia-specifi c primers (O'Neill et al, 1992) was used with a slight modifi cation to the PCR conditions (García-Martínez et al, 1998). Drosophila tristis with known infection status served as a positive control (Erić et al, 2019). To exclude the possible presence of other maternally-transmitted bacteria (Hurst & Jiggins, 2005) we conducted microbiome sequencing.…”
Section: Methodsmentioning
confidence: 99%